Impact of blood flow restriction cuff design on upper body exercise: A randomized crossover trial in resistance‐trained adults - Nicholas Rolnick; Victor S. deQueiros; Brent Fedorko; Samantha Watson; Campbell Ruffhead; Sean Zupnik; Lucas Kuriawa; Mark Weedon; Tim Werner (Physiological Reports)
Abstract Differences in cuff blood flow restriction (BFR) bladder design (single‐chambered [SC‐BFR] and multi‐chambered [MC‐BFR] systems) may influence exercise performance, perceptual responses, and cardiovascular outcomes. In a randomized cross‐over design, twenty‐six healthy physically active individuals (22.6 ± 5.5 years old, 10 females; 25 reported engaging in resistance‐exercise consistently) performed four sets of bilateral biceps curls to volitional failure using 20% of the 1‐repetition maximum under three conditions: SC‐BFR, MC‐BFR, and a non‐BFR control, post‐exercise perceptual responses, and cardiovascular measures pre‐ and post‐exercise. SC‐BFR significantly reduced total repetitions compared to MC‐BFR and N‐BFR (p < 0.001). MC‐BFR and N‐BFR conditions demonstrated comparable performance in later sets. RPD was significantly higher in SC‐BFR compared to MC‐BFR and N‐BFR (p < 0.001), while MC‐BFR elicited lower RPE than SC‐BFR (p = 0.025). Both SC‐BFR and N‐BFR conditions significantly reduced post‐exercise diastolic blood pressure and mean arterial pressure, whereas MC‐BFR did not. No significant differences in PWV were observed across conditions. SC‐BFR induces greater repetition reduction and perceptual discomfort than MC‐BFR, while MC‐BFR demonstrates similar performances and comfort to N‐BFR in later sets. Findings suggest cuff design plays a role in acute BFR responses.